Anestrus in lactating dairy cows before ovulation synchronization - Cartmill, J.A.; Zarkouny, S.E.; Hensley; Stevenson, Jeffrey S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The incidence of anestrus in dairy cattle prior to first inseminations carried out after a minimum of 60 days postpartum ranged from 4 to 58% in first-lactation cows and 14 to 50% in older cows. Dairy cows with more days in milk, older than 2 years, and in better body condition (probably reflective of greater postpartum dry matter intakes) were more likely to cycle than thinner cows. Cows that were not cycling before the first week of insemination conceived at lower rates and took longer to become pregnant.
Keywords: Dairy; Body condition; Cows; Anestrus